Risk of Skin Changes and Sun Protection (Journal of Universal Excellence, 2026)
Research Question (RQ): What are the professionally identified risks of skin changes and what impact does the sun have?Purpose: To present malignant and non-malignant skin changes and risk factors that cause and/or accelerate the occurrence of malignant skin changes, while describing the harmful effects of ultraviolet radiation and the protection against these effects.Method: Professional and scientific literature was studied for the purpose of the research. When searching for resources, we used electronic databases that are accessible to employees at the University of Ljubljana. We restricted our research to professional-scientific peer-reviewed resources with full text that were not older than 10 years.Results: Numerous studies have suggested that excessive sun exposure can be a dangerous activity, which can lead to malignant skin changes. The additional adverse effects of ultraviolet radiation are certainly aided by global climate changes and the resulting depletion of the ozone layer. Despite the known adverse effects, the research has also highlighted the beneficial effects of ultraviolet radiation on human health and well-being.Organization: Healthcare providers will gain structured insights into the risks of skin changes associated with ultraviolet radiation and, at the same time, learn about its beneficial effects on human health and well-being. Society: The sun is extremely important for maintaining life on our planet. Exposure to sun should be done prudently and only at certain times of the day. It is important for society to know both, the harmful and beneficial effects of the sun.Originality: A number of general studies have already been conducted on the research topic. Our research study structurally describes the malignant and non-malignant skin changes and the effect of ultraviolet radiation on their formation.Limitations / further research: We recommend conducting an in-depth research on the awareness of the professional and general population on the effects of ultraviolet radiation.
Keywords: ultraviolet radiation; skin changes; risk factors; protection; awareness